A Primer For Non-Americans On Understanding The Legal System In The United States: Sources, Schools Of Thought, And International Implications - Hunter, Richard J.; Lozada, Hector R.; Shannon, John H. (Archives of Business Research, 2018)
This paper is a primer or introduction to the American legal system prepared especially for those outside the United States who may be called upon to navigate the American legal system. It discusses the origins and functions of American law and its derivation from both the common law system of England and from aspects of the civil law system of continental Europe. The paper delineates the sources of American law, with a special emphasis on the hierarchy of American courts and the principles of supremacy and preemption. The paper then contrasts the American legal system with discreet aspects of international law, based on Article 38 of the Statute of the International Court of Justice, and the Convention on the International Sale of Goods or CISG to which nearly 90 states are signatories. The paper concludes with a discussion of jurisprudence with a focus on the legal philosophies judges bring to the adjudication of actual cases. In addition, the paper provides thumbnail summaries of the major constitutional cases identified in the narrative, as well as references relating to the categorization of the legal systems of nations around the world, an extensive bibliography, and an Appendix containing a list of those nations who have adopted the CISG.